2016
DOI: 10.1038/tp.2016.180
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell inflammatory markers are associated with depressive symptoms in a longitudinal study of urban adults

Abstract: Total white blood cell count (TWBCC) and percentage (%) composition of lymphocytes (PL) or neutrophils (PN) are linked to mid- and late-life depression, though sex-specific temporal relationships between those inflammatory markers and depressive symptoms remain unclear. The association between inflammation and depressive symptoms in longitudinal data on ethnically and socioeconomically diverse urban adults was examined with two hypotheses. In hypothesis 1, we examined the relationship between TWBCC, PL and PN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 67 publications
7
22
0
Order By: Relevance
“…Increases in SNS outflow and NA release following RDS exposure also drives mobilization of lymphocytes from the murine spleen and bone marrow, which then enter the circulation . These data are consistent with the aforementioned findings in humans of increased number of leucocytes in the circulation of individuals with stress‐related psychiatric disorders , and the aforementioned studies reported increases in these cells in the circulation of individuals exposed to ELA. The specific contribution of the rodent models, however, has been to elegantly demonstrate a potential connection between central and peripheral immunity, which highlights the involvement of the SNS.…”
Section: How Does Ela Lead To Immune Activation?supporting
confidence: 88%
“…Increases in SNS outflow and NA release following RDS exposure also drives mobilization of lymphocytes from the murine spleen and bone marrow, which then enter the circulation . These data are consistent with the aforementioned findings in humans of increased number of leucocytes in the circulation of individuals with stress‐related psychiatric disorders , and the aforementioned studies reported increases in these cells in the circulation of individuals exposed to ELA. The specific contribution of the rodent models, however, has been to elegantly demonstrate a potential connection between central and peripheral immunity, which highlights the involvement of the SNS.…”
Section: How Does Ela Lead To Immune Activation?supporting
confidence: 88%
“…Purpose in life has previously been associated with lower levels of single inflammatory markers (17), a finding extended in our study to include further measures known to predict future cardiovascular disease, less healthy aging, poorer mental health, and premature mortality (18, 19). Additionally, we found associations with higher vitamin D concentration, which has been linked with a range of health outcomes, while the inverse relationship with HDL-cholesterol is relevant to reduced cardiovascular disease risk.…”
Section: Discussionsupporting
confidence: 58%
“…One recent study showed a direct relation between total white blood count and depression. In this study, Beydoun et al () proposed that women with increased WBC are more prone to depression whereas the converse was true for men. The authors attributed this differential effect to hormonal effects of stress and cortisol in women.…”
Section: Mechanisms Through Which Infection and Inflammation May Indumentioning
confidence: 59%